Allelopathic Effects of Chickpea on Anatomical Traits of Wheat Varieties Triticum aestivum L - Hussain, Wasan S.; Taher, Noor Al.Huda A.; Abbas, Mahmoud M. (Al-Mukhtar Journal of Sciences, 2021)
This current research deals with the study of the effect of allelopathic compounds of the plant residues of the shoot and root systems of chickpea plants on some anatomical traits of wheat cultivars (Bohoos-4, Debeira, Terbol). It included a study of the anatomical traits of the leaves of the tested wheat varieties and the anatomy of cross-sections of the stems. Results showed differences in the studied traits (number and dimensions of epidermal cells, number and dimensions of stomata, length and number of hairs, frequency and coefficient of stomata) by the effect of plant residues and aqueous extracts treated with them. There was an increase in the number of stomata, stomata coefficient, stomata frequency, hair numbers, and epidermal cell numbers in most of the treatments. Regarding the anatomical traits of stems (section diameter, pith diameter, number and dimensions of bundles) significant differences were noted in the studied characteristics of the cross-section.